Hydraulic performance of sand–clay mixtures: soil fabric perspective. Issue 3 (1st September 2015) - Shaker, A. A.; Elkady, T. Y.
Abstract : Soil fabric plays a fundamental role in the hydraulic conductivity of sand–clay mixtures. Current techniques for the examination of soil fabric are categorised as quantitative (e.g. mercury intrusion porosimetry) or qualitative (e.g. scanning electron microscopy (SEM)), and both types require special equipment and a skilled operator. In addition, during preparation for these techniques, specimen disturbance is of concern. This article introduces a rational approach to evaluate the effect of soil fabric on the hydraulic behaviour of sand–clay mixtures using key void ratios, namely the clay void ratio e c and the skeletal void ratio e sk . A detailed experimental programme was devised to evaluate the hydraulic conductivity of a sand–natural clay mixture under different test parameters (clay content, initial compaction conditions and effective confining pressure). The information on mixture fabric inferred using key void ratios was observed to correlate well with the results of hydraulic conductivity tests. To verify the findings obtained using key void ratios, the particle arrangement within the sand–clay mixture was examined using SEM. SEM micrographs identified different arrangements of sand and clay particles and pore size characteristics depending on clay content in the mixture. These arrangements were consistent with that inferred using key void ratios. Therefore, use of key void ratios can be considered a vital and simple tool to understand the fabric of the studied sand–clay mixture and its impact on design.